2015
DOI: 10.1007/s00259-015-3066-x
|View full text |Cite
|
Sign up to set email alerts
|

68Ga-PSMA imaging of metastatic breast cancer

Abstract: 68 Ga-labelled prostate-specific membrane antigen (PSMA) is rapidly emerging as a significant step forward in the diagnosis of recurrent prostate cancer, based on the fact that PSMA is a type II transmembrane protein with high expression in prostate carcinoma cells [1,2]. Recently it has been demonstrated to accumulate in metastatic clear-cell renal cell carcinoma [3] and interestingly several studies have provided evidence that PSMA is also expressed in the tumour-associated vasculature of primary breast canc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
27
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 64 publications
(30 citation statements)
references
References 5 publications
2
27
0
1
Order By: Relevance
“…The localization of a radiotracer in those cancers appears to be based on PSMA expression in tumor neovasculature (61). Clear cell renal cell carcinoma (62)(63)(64) and cancers of the thyroid (65), breast (66), and colon (67) are among the tumor types reported to have PSMA-targeted radiotracer uptake. With thoughtful, prospective trials to define the clinical utility of PSMA-targeted imaging in these cancers, PSMA-targeted imaging and therapy may prove to have broad implications in the field of oncology.…”
Section: Future Directions For Psma-targeted Management Of Pcmentioning
confidence: 99%
“…The localization of a radiotracer in those cancers appears to be based on PSMA expression in tumor neovasculature (61). Clear cell renal cell carcinoma (62)(63)(64) and cancers of the thyroid (65), breast (66), and colon (67) are among the tumor types reported to have PSMA-targeted radiotracer uptake. With thoughtful, prospective trials to define the clinical utility of PSMA-targeted imaging in these cancers, PSMA-targeted imaging and therapy may prove to have broad implications in the field of oncology.…”
Section: Future Directions For Psma-targeted Management Of Pcmentioning
confidence: 99%
“…Early human clinical studies demonstrated activity in breast tissue (22) and breast carcinoma using 111 In-J591 (23) planar imaging, as well as 68 Ga-PSMA-HBED-CC (N,N9-bis[2-hydroxy-5-(carboxyethyl)benzyl]ethylenediamine-N,N9-diacetic acid) PET/CT ( Fig. 1) (20,(23)(24)(25)(26). For instance, Sathekge et al demonstrated PSMA expression in 84% of 81 suspected metastatic lesions in 19 breast carcinoma patients who were undergoing PSMA-targeted PET imaging (20).…”
Section: Breast Cancermentioning
confidence: 99%
“…Expression in Nonprostate Cancers 1%) (2,8,16,18,21) 74/99 (75%) (2,9,16,18,54)111 In J591 (23,24);68 Ga HBED-CC(20,25) NSCLC 66/420 (16%)(2,15,16,30,31,54) 222/374 (59%)(8,9,30,31,33) …”
mentioning
confidence: 99%
“…In aggregate, our findings in this patient with metastatic clear cell RCC are suggestive that 18 FDCFPyL may able to identify more lesions and has higher tumor uptake than 18 F-FDG. Although a significant body of work has examined the role of 18 F-DCFPyL and other small molecule inhibitors targeted against PSMA in the detection of prostate cancer [1][2][3][4], the use of such radiotracers for non-prostate applications has been limited to date [5,6]. This is despite the fact that PSMA is highly expressed on the tumor neovasculature of many solid tumors, including RCC [7,8].…”
Section: Figurementioning
confidence: 99%